Financial Time Series Modelling of Trends and Patterns in the Energy Markets - Aduda, Jane; Weke, Patrick; Ngare, Philip; Mwaniki, Joseph (Scientific Research Publishing Inc, 2016)
Precise recognition of a time series path is important to policy makers, statisticians, economists, traders, hedgers and speculators alike. The correct time series path is also a key ingredient in pricing models. This study uses daily futures prices of crude oil and other distillate fuels. This paper considers the statistical properties of energy futures and spot prices and investigates the trends that underlie the price dynamics in order to gain further insights into possible nuances of price discovery and energy market dynamics. The family of ARMA-GARCH models was explored. The trends depict time varying variability and persistence of oil price shocks. The return series conform to a constant mean model with GARCH variance.
Keywords: Financial Time Series; Trends and Patterns in Energy Markets; Futures and Spot Prices; ARCH Effects; ARMA-GARCH Models